ESTRATÉGIAS EM GESTÃO DE PESSOAS EM UM HOSPITAL FILANTRÓPICO - Galli, Natália Vogt; De Almeida, Alessandro Jacques; Da Silva, Rafael Dalepiane; Dobler, Jessica Zambom; De Moura, Tainara Uecker; Cichota, Naiara Fetter (Salão do Conhecimento, 2019)
Projeto de Iniciação Científica